ANALISIS KEPUASAN PELANGGAN TERHADAP KUALITAS PELAYANAN JASA PENYEDIAAN CONTACT CENTER PADA PT ABC - Imam Yunianto; Malik Mutoffar; Dyah Kiki Widyaningrum (Jupiter: Journal of Computer & Information Technology, 2022)
In knowing and measuring the level of good acceptance by respondents in the provision of contact center services by PT. ABC and how far the relationship between the provision of contact center services to the interests of customers. Mainly to find out how successful the services are provided and to create a positive image for the company. Satisfactory service, it will be one of the factors that encourage customers to want to use the service again. This study uses a questionnaire to measure the level of customer satisfaction which is implemented using the customer satisfaction index (CSI) method in producing a customer satisfaction index in the provision of contact center services. Samples taken by distributing questionnaires were categorized in terms of importance and customer satisfaction. The results showed that the customer satisfaction index reached 83% based on the criteria for the level of satisfaction, so this number indicates that the customer is very satisfied.